An Unusual Case of Sebaceous Gland Carcinoma Mimicking Recurrent Chalazion in a Young Patient - Mittal, Parul; Gupta, Saroj; Khan, Manal Mohammad; Priyanka, (Nepalese Journal of Ophthalmology, 2026)
Introduction: Chalazion is a common eyelid lesion usually treated conservatively or with minor surgical interventions, such as incision and curettage or intralesional steroid injections. However, recurrent or atypical chalazion in a young adult patient warrants further investigation to exclude malignant conditions such as sebaceous gland carcinoma (SGC). Case: Here an unusual case of SGC presenting with a recurrent chalazion in a young adult patient is reported, which was diagnosed by a biopsy for histopathological examination. Observation: Histopathology revealed sebaceous gland carcinoma. The patient subsequently underwent wide local excision of the lesion, followed by oculoplastic reconstruction. Post-operative follow-up over one year revealed no recurrence or metastasis. Conclusion: This case highlights the importance of considering malignancies like sebaceous gland carcinoma in recurrent or atypical chalazion cases, even in young patients. Early biopsy and histopathological evaluation are essential for timely diagnosis and management to prevent metastasis and ensure better patient outcomes.